Design of metallic phase WS2/cellulose nanofibers composite membranes for light-boosted osmotic energy conversion. (15th November 2022) - Gao, Zongxia; Zhang, Jiajian; Ahmad, Mehraj; Jiang, Bo; Sun, Zhe; Wang, Sha; Jin, Yongcan
Abstract: Osmotic energy reserves in estuaries, coupled with the ubiquitous solar energy, could be harnessed through emerging nanofluidic membranes to reduce the energy crisis. Herein, we mixed WS2 with high concentration of metal phase and cellulose nanofiber (CNF) to fabricate composite membranes by vacuum filtration. Incorporated CNF as space charge donors increases the ion flux through the enlarged interlayer spacing in the WS2 /CNF composite membrane. By simulating seawater and river water, the power density of the composite membrane reached to 1.99 W m −2 . Furthermore, due to the photoelectric characteristics of WS2, the composite membrane exhibits photoresponsivity, which generated a photocurrent of 177 nA through illumination. Taking the advantage of the optoelectronic properties of the composite membrane, the power density under illumination is twice than that of the dark state. Based on the results, this material design strategy can enhance the ion transport in nanofluidic membranes for efficient generation of clean energy.